IPM in Developing Countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Constraints on the adoption of IPM in developing countries - a survey edited by M Iles and A Sweetmore 1991 36pp ISBN 0 85954 299 8 Pbk published by NRI